Phenotypic and genetic variation in resistance to gastro-interstinal nematodes of goats in agro-ecological zones of Limpopo Province - Mohale, Lekukela Bernard (My University, 2019)
The study was conducted to assess phenotypic and genotypic diversity in resistance to gastro-intestinal nematode (GIN) within communal goats in different agro-ecological zones of Limpopo province. Eighty goats were randomly sampled from Mopani = 20, Blouburg = 20, Vhembe = 20 and Capricorn = 20, representing four agro-ecological zones of Limpopo province. Frequencies and percentages of occurrence of qualitative traits and least square means (LSM) of quantitative traits were computed. Goats were characterized as multi-coloured (67.7%), black dominant coat colour (40%), flat face profile (73.8%), erect ears (68.75%), slopping rump (47.5%), no toggles (83.8%), horned (86.3%), while 71.0% and 59.4% were straight shaped and orientated backward respectively, in all agro-ecological zones. Faecal and blood samples were collected to assess the prevalence of GIN and genetic diversity of goats. The highest prevalence and abundance GIN parasites were Haemonchus contortus (nematode = 357.42) followed by Fasciola hapatica (trematode = 163) and Moniezia (cestodes = 121.50). The patterns of GIN prevalence varied (P < 0.05) across agro-ecological zones and seasons. Prevalence of Moniezia nematode varied (P < 0.05) amongst goat sexes, whilst prevalence of other GIN’s did not vary (P>0.05). For genetic variation in GIN resistance, goats were genotyped at 15 microsatellite markers recommended by the International Society of Animal Genetics. Expected heterozygosity (HE) ranged from 0.69 in arid zone goat population to 0.76 in sub-humid zone goat population, while the observed heterozygosity (HO) ranged from 0.53 in arid zone goat population to 0.60 in sub-humid zone goat population. Mean number of alleles (MNA) per population ranged from 6.13 to 7.40. Gene differentiation (FST) among populations was low (3.6%). The results revealed that genetic relationships between populations do not reflect their geographical proximity as revealed by the Nei’s genetic distance results. Low heterozygosity resulted in reducing some fitness traits for GIN parasite resistance. Inbreed goats showed low internal parasite resistance across all agro-ecological zones.
Thesis(M. A. Agricultural Management (Animal Production)) -- University of Limpopo, 2019
Keywords: Capra hircus; Inbreeding co-efficient; Gastro-intestinal nematodes; Phenotypic; Genetic sex determination